GOOGLE WORKSPACE CLOUD SERVICE AS A MEANS OF FORMING PROFESSIONAL COMPETENCIES OF FUTURE MATHEMATICS TEACHERS - Grynova, Марина; Khomenko, Любов (Journal of Information Technologies in Education (ITE), 2023)
The article is dedicated to exploring the role of Google Workspace cloud service in shaping the professional competencies of future mathematics teachers. Modern education increasingly relies on the use of technology in the learning process, including cloud services that provide access to various tools and resources on the Internet, and mathematics teachers need to possess professional competencies that include not only knowledge of mathematics, but also the ability to effectively use modern technologies in the educational process. Google Workspace is one of the leading cloud services that provides a wide range of tools for collaboration, creativity, and organization of work with documents, presentations, archiving, and other tasks that can be useful in the educational activities of mathematics teachers. The key goal is to study the role of Google Workspace cloud service in shaping the professional competencies of future mathematics teachers. Research methods used include analytical analysis of scientific sources, analysis of pedagogical experience, experimental methods, and statistical analysis. Scientific sources related to the concepts of "competence", "professional competence", and "cloud service" were analyzed. The possibilities of using the Google Workspace cloud service in the training of future mathematics teachers were characterized. New opportunities of the set of Internet tools of the Google Workspace cloud service, such as Google Docs, Google Sheets, Google Slides, Google Drive, and others, which can be effectively used in the learning process, were highlighted.